(untitled) (Research, Society and Development, 2020)
Records of aliens species are extremely important, as it indication the new distribution of individuals, helping in future mitigations. The objective is to report a new occurrence of the gastropod Melanoides tuberculata for the Brazilian Amazon region. Specimens were collected at the Praquiquara igarape, located in the middle Apeú river, municipality of Castanhal. This region is directly influenced by agricultural activities and mineral exploration areas, with agriculture and fish farming as its main activities. The individuals were manually sampled in July 2017 and fixed in 70% ethanol. In all, 1,970 were collected. It is estimated that the population density is 7,880 ind./m2, the length classes 10.52 and 16.36 mm correspond to 79.1% of the abundance. It was also found that 87% of the individuals are in their first stage of reproduction. The occurrence of M. tuberculata at Praquiquara igarape, can be restored, since they are still in the initial stage of colonization. Further studies are recommended to monitor the growth and dispersion of the population, in order to determine its real impact.